Moralidade e homicídio: um estudo sobre a motivação e a ação do transgressor - Borges, Luciana Souza (2004)
The objective of this research was to investigate the representation of homicidal subjects as to the reasons of. the crime ( motivation ), and of the crime itself ( action ), not only at the time of the homicide ( past ) as for the present moment as well ( present ), by means of judgement of representation of reality (JRR), and of judgement of moral value (JVM). The sample consisted of 20 men, their ages varying between 30 and 49 years old, in prison and under parole at the Court s Division of Penal Executions of Vitória-ES. Individual interviews were made, according to the clinical method proposed by Piaget ( 1926/s.d.; 1932/1994). From the gathered data, we verifyed that in relation to: 1) the homicidal stories, most crimes took place at night, in public spaces, by fire weapon, against men known to the transgressor, both drunk; 2) as to the motivation for homicide, the JRR emphasized in the present and in the past, the physical aggression which took place, justified in the present mainly because the aggressor felt humiliated, and in the past, because he wanted to take revenge, and the transgressor s or victim s own characteristics; the JVM that was more mentionned in the past, was that their reasons were right due to the characteristics of those interviewed or of the victims, for the suffered humiliations or for the fact that they had to defend a life, whereas in the present, the most cited judgement was that their motives were wrong, in face of. the negative consequences of their crime, and of the religious arguments; 3) as to the action of the homicide, the JRR most mentionned in the past , was that those who had committed it, would do it again, either for the suffered humiliation or for the feeling they had experienced; and in the present they mentionned that they wouldn t kill again, due to the negative consequences of the crime, to the victim s own characteristics, and to religious motives; the JVM more mentionned in the past was that the action would be wrong, because of. the negative consequences, whereas in the present all of them judged as wrong the committed homicide, due to negative consequences, to the value attributed to life, and to religious motives; 4) as to the data in general , there was a greater tendency in condemning the homicide, and not its motivation; the religious arguments were linked to the fact that in the present , those interviewed judged as wrong the motivation and the action for the crime, and therefore they wouldn t do it again; the explanations linked to humiliation belongs mainly to the past, so as to justify as correct the judgement of value of the motivation and of the action, as a reason for why at that time, they would commit homicide again, as an action for honour .